Inverted Papilloma: Our Experience of Endoscopic Medial Maxillectomy and its Outcome in a Tertiary Care Center, Nepal - Basnet, Meenakshi; Thakur, Sanjeev Kumar; Ghimire, Bibek; Nepal, Niraj (Journal of Nobel Medical College, 2020)
Background: Inverted Papilloma arises from the lateral wall of nose and is common in maxillary sinus. It is locally invasive, can recur and has malignant potential. Endoscopic medial maxillectomy is the preferred choice. Materials and Methods: This prospective study was conducted in the department of Otolaryngology, Nobel Medical College and Teaching Hospital, Biratnagar from June 2015 to June 2018. A total of 26 patients were included in the study, after informed consent and ethical clearance. Staging was done by Krouse method after imaging studies and preoperative endoscopic biopsy was performed. These patients then underwent endoscopic medial maxillectomy. All the data were collected in excel spreadsheet and analyzed in SPSS software. Results: Out of a total of 26 patients, male: female ratio was 1.6:1, with 16 male and 10female. Average age was 40.5 years (25-72years). According to Krouse staging, 2 patients were in Stage I, 7 patients in Stage II and 17 patients in Stage III. IP mostly involved the lateral wall of nose. Unilateral nasal obstruction was the commonest presenting symptom. The commonest post-operative complication was nasal crusting. Most of the patients were treated with simple endoscopic medial maxillectomy. Conclusion: Inverted Papilloma is common in male in their 4th decade of life with lateral wall of the nose being mostly affected. Most patients were in stage III of Krouse’s staging system. Simple endoscopic medial maxillectomy was the commonest procedure.